Media Sosial: Perubahan Sosial Budaya dan Dampaknya pada Masyarakat (International Forum of Researchers and Lecturers, 2024)
Social media is not just a communication tool; it is a major force that shapes and changes social and cultural patterns in contemporary society. Its presence, as a result of advances in information technology in this era of globalization, not only changes the way we communicate, but also creates a deep transformation in the structure of social values and societal norms. These changes involve not only practical aspects, such as lifestyle, but also include the basics of behavior and worldview.With social media, we have entered an era where information can quickly and easily spread throughout the world. This opens the door to unprecedented global connectivity, allowing people to interact without the barriers of distance and geographical boundaries. However, behind this convenience, there are significant changes in the way we view and appreciate cultural values. The advantages of social media include its ability to accelerate the flow of information, facilitate intercultural interactions, and provide a platform for previously unheard voices. The spread of false information or hoaxes has become easier, and the impact on mental health, especially among the younger generation, is a serious concern.